1990
DOI: 10.2527/1990.6882414x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extrusion on the ileal and fecal digestibilities of lysine in yellow corn in diets for young pigs.

Abstract: Forty crossbred barrows (initial avg BW of 20 kg) were fitted with T-cannulas to determine the effects of extrusion of yellow corn on lysine digestibility. A basal corn-cornstarch-soybean meal diet was formulated to contain .55% lysine. Extruded corn (EC), non-extruded corn (C) and L-Lysine-HCl (LLH) replaced cornstarch in the basal diet to provide total dietary lysine levels of .60, .65 and .70% lysine for each lysine source. Diet intake was 5.5% of BW. Treatments were arranged as a 3 x 3 factorial with the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
17
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 14 publications
11
17
0
2
Order By: Relevance
“…In the present study, extrusion of maize and sorghum did not improve the ileal digestibilities of amino acids, with the exception that the digestibility of Met in sorghum was improved (P<0.05) in EW pigs as compared with ground maize or sorghum. This result is in partial agreement with previous studies for maize (Herkelman et al, 1990) and sorghum (Noland et al, 1976). Herkelman et al (1990) reported that extrusion improved energy utilisation but did not affect utilisation of lysine or N in maize by growing pigs.…”
Section: Grain Processing and Ileal Digestibilitysupporting
confidence: 83%
See 2 more Smart Citations
“…In the present study, extrusion of maize and sorghum did not improve the ileal digestibilities of amino acids, with the exception that the digestibility of Met in sorghum was improved (P<0.05) in EW pigs as compared with ground maize or sorghum. This result is in partial agreement with previous studies for maize (Herkelman et al, 1990) and sorghum (Noland et al, 1976). Herkelman et al (1990) reported that extrusion improved energy utilisation but did not affect utilisation of lysine or N in maize by growing pigs.…”
Section: Grain Processing and Ileal Digestibilitysupporting
confidence: 83%
“…This result is in partial agreement with previous studies for maize (Herkelman et al, 1990) and sorghum (Noland et al, 1976). Herkelman et al (1990) reported that extrusion improved energy utilisation but did not affect utilisation of lysine or N in maize by growing pigs. Noland (1976) also reported that extrusion improved energy digestibility of high tannin sorghum grain when fed to nursery pigs.…”
Section: Grain Processing and Ileal Digestibilitysupporting
confidence: 83%
See 1 more Smart Citation
“…A atividade ureática do farelo de soja expandido foi inferior ao nível mínimo mencionado, indicando, portanto, efeitos do superprocessamento. Os baixos valores de atividade ureática do farelo de soja expandido coincidem com os resultados de proteína solúvel e da solubilidade da proteína em KOH neste alimento, semelhante ao encontrado por Araba e Dale (1989;1990). Segundo Van Soest (1994), parte do nitrogênio estaria em forma não utilizável no trato gastrintestinal dos animais, atribuído à redução da taxa de hidrólise protéica, impedindo o acesso das proteases.…”
Section: Methodsunclassified
“…Therefore, the utilization of energy may be greater in pigs fed extruded corn versus raw corn. However, the ileal digestibility of lysine or nitrogen in extruded corn is not different from that in raw corn (Herkelman et al, 1990;Chae et al, 2000). Dietary fibre reduces energy and nutrient digestibility by pigs and as a consequence, increases fecal mass and nutri-ent excretion (Shi and Noblet, 1994;Canh et al, 1998;Davidson and McDonald, 1998).…”
mentioning
confidence: 99%